Analisis Womenpreneur Leadership dalam Menjalankan Organisasi - Desri, Syuryatman; Lorenzha, Maharani; Maharani, Riska (Lembaga Yasin AlSys, 2023)
Leaders of companies or organizations are mostly led by men. But now, a woman can lead a business. Every leader, whether male or female, has a certain way of being a leader. Gender is a factor in how a woman feels valued. There are four types of women's empowerment, namely women's empowerment through feminism, women's empowerment through transactivism, and women's empowerment through transformation. The purpose of this research is to analyze the characteristics of female leadership applied in an organization. . The type of analysis used is quantitative descriptivism. Among these leadership styles, the leader who is dominant in the transformational leadership style is clearly visible when compared to the transactional leadership style. However, among the feminine and transformational leadership styles, leaders tend to show greater dominance in the use of the feminine leadership style. This is because leaders are people or team oriented individuals and have charisma.